2010
DOI: 10.1118/1.3490086
|View full text |Cite
|
Sign up to set email alerts
|

Apparent absence of a proton beam dose rate effect and possible differences in RBE between Bragg peak and plateau

Abstract: Present RBE can be consistently used in treatment planning of PRT using ultrahigh dose rate radiation. Because a significant increase in RBE toward the Bragg peak was observed for both UDR and CDR, further evaluation of RBE enhancement toward the Bragg peak and beyond is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Clonogenic assays in vitro have long shown that the cell killing effectiveness of sub-millisecond pulses of relativistic electrons [reviewed in (18)] or protons (4,19) does not differ significantly from that of continuous x-ray irradiation at a conventional dose rate. However, these studies did not pay attention to the mechanisms of radiationinduced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Clonogenic assays in vitro have long shown that the cell killing effectiveness of sub-millisecond pulses of relativistic electrons [reviewed in (18)] or protons (4,19) does not differ significantly from that of continuous x-ray irradiation at a conventional dose rate. However, these studies did not pay attention to the mechanisms of radiationinduced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal proton beams were accelerated up to 190 MeV by an Azimuthally Varying Field (AVF) cyclotron at the NCCHE (National Cancer Center Hospital East) [31]. In this experiment, we used the nozzle designed for the dual-ring scattering method [24] to obtain a flat dose profile and stable dose intensity over the target area.…”
Section: Methodsmentioning
confidence: 99%
“…3). The RBE at 10% survival for Chinese hamster fibroblasts and two human squamous cell carcinomas ranges between 1 and 1.2, much lower than the RBE values for these same cells relative to low-energy protons [20] or heavy ions [22], but similar to the value of 1.1 normally used in Bragg peak proton therapy [23] and measured in radiobiological experiments [2426]. Similarly low RBE for 1-GeV protons has been also measured for white blood cell loss in mice [27].…”
Section: Discussionmentioning
confidence: 89%